Participative management in enhancing work performance: an analysis towards employees of HICOM-HONDA (M) Manufacturing Sdn. Bhd., Sungai Petani, Kedah / Mazidah Mansor and Salmiyati Md Raus - Mansor, Mazidah; Md Raus, Salmiyati (2010)
Many manufacturers have implemented a participative management to enhance the performance of employees because nowadays traditional “top down” approaches are unlikely to achieve the performance enhancement. Participative management addresses fundamental issues within organization and the role of employees and external stakeholders in all levels of organizational decision making. It helps to let manager deal with the employee in contribute towards organizational performance. The implementation of participative management by apply strong engagement relationship among organization’s members, worker empowerment and participative in decision making heading toward enhancing organizational performance. Besides that, participative management plays a vital role in employee development in an organization. Formal patterns of participation need to be truly implemented where employees have a right to contribute on all levels of decision making. Thus, paper discuss regarding the factors influence towards organization performance by applying elements in participative management such as empowerment, engaging employee relationship and collective decision-making.